Analysis of the Interactive Effects of Drivers on the Development of Marketing Agility in Educational Services in Iran - Entezari, Farid; Hataminasab, Seyyed Hassan; Nayebzadeh , Shahnaz (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The increasing changes in the field of educational services, along with the heightened competitive power of organizations active in this domain, have compelled them to exhibit greater dynamism and flexibility. Therefore, possessing marketing agility is essential and a competitive advantage for educational service centers. This research aims to identify the factors influencing the development of marketing agility in Iran’s educational services. Methodology: Using a mixed-method approach, it seeks to identify these factors to enhance and develop educational marketing performance by extracting how these factors affect each other. For this purpose, data collection and evaluation were conducted using three methods: content analysis, Delphi analysis, and interaction effects analysis, based on data from previous articles and research, and expert evaluations using questionnaires. Findings: The results indicate that seven factors of marketing agility in Iran’s educational services are of significant importance, among which culture has the most influence, and dynamism is the most influenced. Additionally, the indirect effects of technology on dynamism, competence on dynamism, and competence on management are also relatively significant. Conclusion: The indirect effects matrix analysis also shows that, besides the indirect effect of technology and competence on dynamism, they also indirectly influence management, with competence having a more significant impact.